Photoacoustic Force‐Guided Precise and Fast Delivery of Nanomedicine with Boosted Therapeutic Efficacy. Issue 16 (3rd June 2021) - Wang, Jun; Li, Tingting; Ni, Jen‐Shyang; Guo, Heng; Kang, Tianyi; Li, Zeshun; Zha, Menglei; Lu, Songbo; Zhang, Chen; Qi, Weizhi; Xi, Lei; Li, Kai
Abstract: Precise and efficient delivery of nanomedicine to the target site has remained as a major roadblock in advanced cancer treatment. Here, a novel photoacoustic force (PAF)‐guided nanotherapeutic system is reported based on a near‐infrared (NIR)‐absorbing semiconducting polymer (SP), showing significantly improved tumor accumulation and deep tissue penetration for enhanced phototherapeutic efficacy. The accumulation of nanoparticles in 4T1 tumor‐bearing mice induced by the PAF strategy displays a fivefold enhancement in comparison with that of the traditional passive targeting pathway, in a significantly shortened time (45 min vs 24 h) with an enhanced penetration depth in tumors. Additionally, a tumor‐bearing mouse model is rationally designed to unveil the mechanism, indicating that the nanoparticles enter solid tumors through enhanced transportation across blood vessel barriers via both inter‐endothelial gaps and active trans‐endothelial pathways. This process is specifically driven by PAF generated from the nanoparticles under NIR laser irradiation. The study thus demonstrates a new nanotherapeutic strategy with low dose, enhanced delivery efficiency in tumor, and boosted therapeutic efficacy, opening new doors for designing novel nanocarriers. Abstract : A novel photoacoustic force‐guided nanotherapeutic system based on a near‐infrared‐absorbing semiconducting polymer is reported, showing significantly improved tumor accumulation and deep tissue penetration for enhanced therapeutic efficacy.